Creative Cutouts: Integrating Kirigami as a Learning Media to Enhance Fine Motor Skills in Kindergarten Children - Istirokah Istirokah; Sulis Janu Hartati; Edy Widayat; Nuril Huda; Nensy Megawati Simanjuntak; Sarah Prather (CV. Media Inti Teknologi, 2025)
Background: Fine motor skills are fundamental to a child's early development, influencing their ability to perform daily academic and self-care tasks. However, traditional methods for developing these skills in kindergartens often lack creative andengaging approaches. Kirigami, the Japanese art of cutting and folding paper, has the potential to serve as an interactive learning medium that promotes fine motor skill development through artistic expression and hand coordination.Aims: This paper aims to examine the effectiveness of integrating kirigami as a learning medium to enhance fine motor skills in kindergarten children. The scope includes evaluating improvements in muscle control, hand-eye coordination, and paper manipulation abilities through structured kirigami activities.Methods: The study employed a quasi-experimental design involving 30 children aged 4–6 years, divided equally into an experimental group and a control group. The experimental group received four weeks of kirigami-integrated sessions, while the control group followed conventional fine motor activities. Pre-test and post-test assessments were conducted using a standardized fine motor rubric. Data were analyzed using paired and independent t-tests.Results: The results showed a statistically significant improvement in fine motor skills in the experimental group compared to the control group. Notable gains were observed in scissor control, grip strength, and spatial accuracy. Additionally, qualitative observations indicated increased engagement and enjoyment during kirigami activities.Conclusion: Integrating kirigami into early childhood education serves as an effective, low-cost learning media to enhance fine motor development. It not only supports motor coordination but also fosters creativity and concentration. The study recommends adopting kirigami as a regular component of kindergarten curricula.